Avaliação de programa de educação positiva com recursos tecnológicos para mães que agridem fisicamente - Santini, Paolla Magioni (2015)
This thesis involves a compilation of scientific texts and comprises four manuscripts: one book chapter and three Journal papers. Such texts are articulated in order to structure the theoretical support, the development and evaluation of an intervention program to mothers who use corporal punishment, suggesting improvements for future research. The definition of corporal punishment was initially presented, as well as a brief overview of this disciplinary practice in Brazil, identifying strategies to curb and prevent it. A systematic review the Brazilian and international literature on parenting programs focused on the prevention of corporal punishment follows, suggesting the need to develop more programs on this theme with solid methodological rigor. In sequence, the sociodemographic profile, history of violence and disciplinary practices of 40 mothers who use corporal punishment was determined, finding that the mothers justified the physical violence towards the children by nervousness , demonstrating an urgent need to receive specialized guidance. Finally, the program involving Project Parceria s second Unit on Positive Parenting of Children was described in detail, including technological resources: coaching and videofeedback of videotaped mother-child interaction sessions, in a randomized controlled trial. Significant positive results in the post-test measures of mothers in the experimental group were observed in comparison to the control group, regarding decrease of depression scores, increase of children's strengths, as well as diminished behavior problems and hyperactivity. In addition, there was a significant improvement in mother-child positive interaction measured in observation sessions at post-test.